Ecto and intestinal parasites of wild dwelling Rattus rattus in Sri Lanka. - Ratnaweera, P B; Wijesinghe, M R; Udagama-Randeniya, P V (Thirteenth International Forestry and Environment Symposium, Sri Lanka, pp 63., 2008)
history. E. singhala restricted to undisturbed forest patches of Caryota urens, Calamus rotang and Calamus zeylanicus in wet zone highland but the absence of the species after extensive survey in similar habitats reveal that E. singhala is more local. E. singhala is rather shy butterfly inhabits dark dense forests which feeds on over-ripped fruits etc.. E. singhala often fly as couple and individual female can be seen hovering host plats. E. hypermnestra female always flies individually and less abundant than its male. E. hypermnestra males pare have a 'dance' or 'fight' possibly for territory. Perhaps pare of males share the same territory because both chase other butterflies together and that 'couple dance' never aggressive. Immediate conservation actions such as habitat restoration and transplanting should be tested for E. singhala.